Cuticular hydrocarbons are associated with mating success and insecticide resistance in malaria vectors - Kelsey L. Adams (Nature Portfolio, 2021)
In this study, Adams et al. investigate the effect of cuticular hydrocarbons on mating success in natural mosquito mating swarms. These hydrocarbons confer both higher mating success and increased resistance to pyrethroid, suggesting sexual selection for insecticide resistance in this population secondary to mating success.